2000
DOI: 10.1159/000028371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Am-80, a Retinoid Derivative, on 2,4-Dinitrofluorobenzene-Induced Contact Dermatitis in Mice

Abstract: Retinoids have many pharmacological activities, including anti-inflammatory action and antiangiogenesis, effected through the regulation of various gene transcriptions. In this study, we investigated the effect of Am-80, one of the retinoic acid derivatives, on hapten-induced contact hypersensitivity in BALB/c mice. After application of 2,4-dinitrofluorobenzene (DNFB) to the ears of the mice, severe contact hypersensitivity with marked infiltration of inflammatory cells and hypertrophy of the epidermis was cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…on September 11, 2016. by guest www.bloodjournal.org From induced contact dermatitis, 22 and atherosclerosis. 23 Because retinoids can down-regulate Th1 and Th17 cells and can ameliorate autoimmune diseases, we hypothesized that these retinoids would attenuate cGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…on September 11, 2016. by guest www.bloodjournal.org From induced contact dermatitis, 22 and atherosclerosis. 23 Because retinoids can down-regulate Th1 and Th17 cells and can ameliorate autoimmune diseases, we hypothesized that these retinoids would attenuate cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…28 Am80, a novel RAR␣/␤-specific synthetic retinoid, has a biologic activity ϳ 10 times more potent than that of ATRA 20 and directly inhibits Th1 cytokine production. 20,22,29 Therefore, we hypothesized that ATRA or Am80 downregulates both Th1 and Th17 differentiation in donor T cells, resulting in attenuation of cGVHD. To clarify whether retinoids directly inhibit the production of cytokines, PLNs were isolated from mice 14 days after allogeneic BMT and cultured with Am80 for 24 hours to determine cytokine production.…”
Section: Am80 Inhibits Donor Th1 and Th17 Cells Both In Vitro And In mentioning
confidence: 99%
See 1 more Smart Citation
“…Am80 has been reported to inhibit the development of collagen-induced arthritis in mice and rats, experimental autoimmune encephalomyelitis in rats and 2,4-dinitrofluorobenzene-induced contact dermatitis in mice. [9][10][11][12] In this study we examined the effect of Am80 administration on the development of type 1 diabetes in NOD mice in order to clarify its immunomodulatory competence.…”
mentioning
confidence: 99%
“…8 Am80 is also known to inhibit the IL-6 signaling. 9 -11 Am80 suppresses IL-6 production in splenic mononuclear cells and reduces the severity and progression of inflammatory disease models, including 2,4-dinitrofluorobenzene-induced contact dermatitis, 10 collageninduced arthritis, 11 and allergic encephalomyelitis. 9 Recently, we reported that Am80 inhibits neointima formation in a mouse vascular injury model, suggesting it also modulates inflammatory and remodeling processes in the vessel wall.…”
mentioning
confidence: 99%